(untitled) (Contemporary Journal of Social Science Review, 2025)
This study investigated views of parents regarding the cultural relevance of early childhood curricula in private preschools. Early childhood education is recognized as laying the foundation for a child’s lifelong learning, and the role of parents—as children’s first educators—is considered very important in shaping their values, identity, and development. However, many preschool curricula in Pakistan remained disconnected from the cultural contexts of the children they served. This research aimed to explore how parents perceived cultural appropriateness of the curriculum used in their children’s early education and to identify areas where alignment with home culture could be strengthened. The study employed a qualitative case study approach involving three private early childhood education centers in Karachi. Purposive sampling was used to select 15 parents from diverse cultural backgrounds. Data was collected through semi-structured interviews and analyzed thematically to identify recurring ideas and insights. Key findings revealed that parents highly valued inclusion of their cultural values, languages, and traditions in the curriculum. They expressed concern over dominance of Western content and absence of local stories, festivals, and values in the teaching materials. Parents also emphasized importance of developing a curriculum that supported children’s holistic development—including identity, self-esteem, and emotional well-being—by reflecting their cultural heritage. Findings suggested that involving parents in curriculum planning could lead to more inclusive and meaningful learning experiences. Recognizing parents as key stakeholders, would foster a stronger home-school connection and ensure that early education promotes cultural pride and understanding. Study recommended integrating local languages, customs, and values into curriculum development, and urged policymakers and educators to adopt culturally responsive practices in early childhood education.